Linguodidactic framework of teaching russian intonation to a multinational audience in light of experimental data - Khromov, Sergey Sergeevich; Shutova, Marina Nikolaevna; Nesterova, Tatyana Vyacheslavovna (Universidade Estadual Paulista, 2021)
The article deals with the linguodidactic framework of teaching Russian intonation to foreign students, in particular, the intonation of the general question which presents the most difficulty for students of different nationalities. The authors analyze an experiment aimed at identifying the difficulties in intoning the general question for speakers of tone and non-tone languages. During the experiment, the authors identify universal (core) intonational characteristics that manifest regardless of nation-specific (idiomatic) language features. Such features include not only the set of secondary melodic traits but also indicators of intensity and duration as well as formant features of nuclear syllables.